Music performance anxiety: a critical review of etiological aspects, perceived causes, coping strategies and treatment - BURIN, ANA BEATRIZ (2017)
Background Music performance anxiety (MPA) is understood as a sub-type of social anxiety and is characterised by fears of a musical presentation. Objective To carry out a critical literature review on clinical and etiological aspects, perceived causes, coping strategies and treatment of MPA. Methods Electronic databases PubMed, PsycINFO and Lilacs as well as specific periodicals were used based on the key-words symptoms, diagnosis, aetiology, perceived causes, coping strategies and treatment. Results MPA is highly prevalent among musicians (>; 16%), regardless of culture and formation. Cognitive, behavioural and physiological factors are associated with the aetiology of MPA, including biological and psychological predispositions. In addition, one should highlight factors related to the individual, aspects related to tasks and musical situation as perceived causes and/or predictor variables of MPA. As for the coping strategies, one can also highlight the use of breathing/relaxing techniques, increased musical practice, use of homeopathy and substances without medical prescription. Discussion MPA is impacting in the musician’s life. Despite the increasing interest in its study, it is necessary to better understand this complex phenomenon, mainly in the therapeutic context, in addition to the publicising and offering of services for prevention and treatment of MPA.